TRPV1 and TRPV1-Expressing Nociceptors Mediate Orofacial Pain Behaviors in a Mouse Model of Orthodontic Tooth Movement - Wang, Sheng; Kim, Martin; Ali, Zayd; Ong, Katherine; Pae, Eung-Kwon; Chung, Man-Kyo (Frontiers in Physiology, 2019)
Orthodontic force produces mechanical irritation and inflammation in the periodontium, which is inevitably accompanied by pain. Despite its prevalence, treatment of orthodontic pain is ineffective. Elucidating underlying neural mechanisms is critical to improving the management of orthodontic pain. We have assessed the contribution of transient receptor potential vanilloid subtype 1 (TRPV1) and the TRPV1-expressing subset of nociceptive afferents to pain behaviors induced by orthodontic force in mice. Microfocus x-ray computed tomography analysis showed that application of an orthodontic force of 10g to the maxillary first molar produced reliable tooth movement in mice. Mouse grimace scale (MGS) was evaluated as an indication of non-evoked spontaneous pain and bite force (BF) was measured for assessing bite-evoked nocifensive behaviors. Orthodontic force increased MGS and decreased BF, both of which were interpreted as increased levels of pain. These behaviors peaked at 1d and returned near to the sham level at 7d. Retrograde labeling and immunohistochemical assays showed TRPV1-expressing peptidergic afferents are abundantly projected to the periodontium. Direct injection of resiniferatoxin into trigeminal ganglia (TG) decreased TRPV1-expressing afferents by half in the targeted region of TG. The chemical ablation of TRPV1-expressing afferents significantly attenuated orthodontic pain behaviors assessed by MGS and BF. Consistently, the knockout of TRPV1 also attenuated orthodontic force-induced changes in MGS and BF. These results suggest that TRPV1 and TRPV1-expressing trigeminal nociceptors constitute a primary pathway mediating orthodontic pain behaviors in mice. This model will be useful for mechanistic studies on orthodontic pain aimed at developing novel approaches for painless orthodontics.